Protection of forest genetic resources by intellectual property rights – exploring possibilities and conceivable conflicts*. Issue 7 (3rd October 2017) - Myking, Tor; Walløe Tvedt, Morten; Karlsson, Bo
ABSTRACT: The world's need for industrial wood is expected to greatly increase in coming decades. Somatic embryogenesis (SE) is a way in which an almost unlimited number of genetically identical plants (clones) can be produced from a single mother plant/seed, and it offers an effective way to convey the genetic gain obtained in breeding to the planting stock. As cultures or methods of SE, for example in Norway spruce ( Picea abies ), may become the subject of intellectual property rights (IPRs), a legal conflict may arise between the right holder and the rights of the general public covered by the Every man's rights to freely sample, for example, forest genetic resources (FGRs). Various IPR systems may be relevant for the protection of SE material in forestry, but they possibly differ in how well sufficient genetic variation can be encompassed by protection claims. We therefore specifically advocate awareness of genetic variation in future SE-related IPR claims in forestry, and argue that process patents are most applicable. In face of the bioeconomy, it is mandatory to be aware of the possible conflicts between IPRs and rights of the public to FGRs, and the genetic variation of future IPR-protected SE material in forestry.